Unresolved wheeze in a child: A rare case of misdiagnosed chronic airway obstruction - Dongol, Jenu Suwal; Ghimire, Anand; Ghimire, Amrit (Grande Medical Journal, 2025)
Foreign body aspiration (FBA) in children can often present with subtle symptoms that closely resemble common respiratory conditions such as asthma or pneumonia, leading to potential misdiagnosis. This case report is about a four-year-old boy who had ongoing breathing problems and was treated for almost a year before the real cause was diagnosed: a yak bone stuck in his airway. The diagnosis was ultimately made at Grande International Hospital, a year after the initial aspiration. This case underscores the diagnostic challenges in resource-limited settings and highlights the importance of maintaining a high index of suspicion when standard treatments fail to resolve symptoms.